Ligamentum Teres Hepatis Tunnel (Pons hepatis) in Human Liver: A Case Report from Nepal - Shrestha, Sunil; Sharma, Nitasha; Shah, Ajay (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION The liver, the biggest gland with diverse metabolic activity consist right and left lobe, where left lobe was isolated from quadrate lobe by umbilical or ﬁssure for ligamentum teres exhibits variation. The case reported explains about the liver tissue bridge, a 2 cm long creating incomplete tunnel that connect the quadrate lobe to the left lobe corresponding to type 4 b variation of Pons hepatis. As a result, the tunnel may depict a deceptive impression of a diseased cavity due to liver parenchyma and confuse surgeons and pathologist.